PI-based composites with high dielectric constant and low loss by filling with self-derived carbon. (March 2023) - Li, Ke; Peng, Mingyun; Yu, Qiyu; Huang, Bingliang; Cheng, Jie
In this work, we prepared polyimide (PI) composite films by directly filling the matrix with self-derived carbon particles. Without any surface modification layer, these specially made particles were compatible with their parent matrix quite well. For the composite film with 25 wt% filler content, the dielectric constant was 72.5 at 1 MHz at room temperature, and the dielectric loss was only 0.069. The conductivity of the corresponding composite was measured to be below 10 −6 Sm −1, and the breakdown strength was 165 MVm −1 . In addition, the tensile strength of the composite film was measured to be 73 MPa. These results indicate that carbonized PI can be used as an excellent filler to prepare PI-based composite films with high dielectric constant.